Analysing the effect of portfolio concentration index and stock market correlation - Lee, Pei Ling; Lee, Chin; Siong, Hook Law; Wan Ngah, Wan Azman Saini (Penerbit Universiti Kebangsaan Malaysia, 2019)
The objective of this research was to test the effect of portfolio concentration on market correlation. The relationship between stock market linkages and portfolio concentration was investigated to gain a better understanding of the vulnerability that a country is subjected to during a global financial crisis. The portfolio concentration index of a country reflects its portfolio investment strategy and design, whether it prefers to concentrate its portfolio of stocks in a handful of target markets or to geographically diversify its investments. It was found that countries that had invested disproportionate weights in selected financial markets were significantly different from those countries that held less concentrated portfolios in terms of their effect on financial market integration. The portfolio concentration index, real interest rate differential, industrial production growth differential, and stock market size differential were statistically significant in influencing the correlation in stock returns when a fixed effects model was employed for a sample of 25 investing and 27 investee countries from 2001 to 2014. This study implied that although portfolio allocation affects financial market integration, it is not significantly related to financial spill-overs during crisis periods. The findings may shed light for investors regarding portfolio designs and allocation decisions.